Ischemic heart disease burden attributable to inadequate omega-3 fatty acid intake in Chinese adults, 1990–2021: an Age-Period-Cohort analysis of the Global Burden of Disease study - Luo, Lin (Frontiers in Nutrition, 2025)
BackgroundInsufficient omega-3 fatty acid intake is a significant modifiable risk factor for ischemic heart disease (IHD), yet its long-term impact on the disease burden in the Chinese population remains inadequately understood. This study, based on data from the Global Burden of Disease (GBD) study, is the first comprehensive analysis of the Age–Period–Cohort (APC) dynamics of IHD burden attributable to insufficient omega-3 intake in Chinese adults from 1990 to 2021, revealing age- and sex-related heterogeneity and social determinants.MethodsData from the GBD 2019 study on Chinese adults aged 25–94 years, stratified by sex, were integrated. The age-period-cohort (APC) model was employed to analyze the spatiotemporal dynamics of death and disability-adjusted life years (DALYs), with net drift and local drift metrics used to quantify long-term trends.ResultsIn 2021, the death rate from IHD attributable to insufficient omega-3 intake demonstrated an exponential age gradient, with death increasing from 5.568 per 100,000 in the 25–29 age group to 3,806.93 per 100,000 in the 90–94 age group (a 684-fold increase). Male death (708.01 per 100,000) was significantly higher than female death (537.28 per 100,000), with sex differences following a nonlinear age pattern: male death was 54–78% higher than female death in younger and middle-aged adults, while female risk exceeded male risk in the 70–84 and 90–94 age groups. The DALY rate exhibited a critical turning point between the ages of 45 and 50 (30 → 475 per 100,000), with greater health risk heterogeneity observed among men (standard deviation 145.65 vs. 96.24 in women). From 1990 to 2021, the absolute number of deaths increased by 17.47%, while age-standardized death decreased by 19.72% (from 7.28 to 5.84 per 100,000), and the DALY rate declined by 41.40% (from 221.39 to 129.75 per 100,000). The APC model revealed: (1) Age effect: Death in the 90–94 age group reached 3,806.93 per 100,000, emphasizing the risks associated with extreme aging; (2) Period effect: A sharp 10% decrease in DALYs in the middle-aged group during 2005–2006, coinciding with strengthened nutrition policies; (3) Cohort effect: Death in the 1895–1994 birth cohort declined by 99.3%, reflecting progress in public health. Net drift analysis showed that the annual decline in DALY rate (−1.53%) was significantly greater than the death decline (−0.32%), with the most notable improvement in the middle-aged group (local drift of −3.87% per year).ConclusionThis study is the first to reveal the dynamic evolution of IHD burden attributable to insufficient omega-3 intake in China. Although both death rates and DALY rates have decreased, population aging continues to drive an increase in the absolute disease burden. By innovatively integrating Age–Period–Cohort modeling with nutritional epidemiology, this study provides multidimensional evidence to inform age- and sex-specific intervention strategies and to guide the refinement of dietary guidelines.